Study of the dynamics of preparedness indicators for highly skilled kayakers during the training process - Pogrebnoy, A.; Makarova, G.; Karpov, A.; Komlev, I. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to identify the dynamics of technical and physical fitness indicators of highly skilled kayakers when performing various training loads during the preparatory period.